PERTIMBANGAN HAKIM MAHKAMAH AGUNG DALAM PERKARA KEKERASAN TERHADAP ANAK YANG MENYEBABKAN KEMATIAN - Rachmayanti, Maya Arum; Rustamaji, Muhammad (Sebelas Maret University, 2026)
This article aims to find out whether the consideration of the Supreme Court judges in correcting the decision of the high court in the case of violence against children that causes death is in accordance with Article 253 paragraph (1) of the KUHAPThis legal research uses normative legal research methods that are prescriptive and applied using a case study approach by examining one case of criminal violence against children with the Supreme Court Decision Number 3789/K/Pid.Sus/2023. The collection of legal materials is carried out by means of literature studies and the legal materials used are primary and secondary legal materials. The analysis technique that the author uses is to use the deduction method of syllogism, from the submission of major premises and minor premises that are connected to each other so that conclusions can be obtained. Based on the results of research and discussion that has been carried out by the author, the consideration of the Supreme Court judge to correct the High Court's decision is based on the elements contained in Article 253 of the Criminal Procedure Code. However, in this study it can also be concluded that the High Court judge in handing down the verdict was not fully in accordance with the provisions in Article 253 of the KUHAP.